Study on the relationship between lid-parallel conjunctival folds and symptoms and signs of dry eye disease - Meng, XiangTian; Zhou, Hongyan (Frontiers in Medicine, 2025)
PurposeThe aim of this study is to explore the correlation between grade and total number of nasal and temporal side lid-parallel conjunctival folds (LIPCOFs) for signs and dry eye severity grading of different types of dry eye disease.MethodsThe data of 76 eyes of 38 patients with dry eye disease were selected. Fluorescein Breakup Time (FBUT), tear secretion function, corneal staining test, and slit lamp examination were performed. The above results, including the grade and the total number of nasal and temporal side LIPCOFs, were recorded. The causal relationship between parametric variables was analyzed by Pearson’s correlation, and the causal relationship between non-parametric variables was analyzed by Spearman’s correlation. Paired t-test was used to analyze statistical differences between different groups. Benjamini-Hochberg False Discovery Rate (BH-FDR) correction is used to reduce the risk of type I error rate inflation when there is a correlation between multiple indicators.ResultsA significant negative correlation was found between the grade of temporal side LIPCOF and the FBUT in all 76 eyes, both in the aqueous deficiency group and the non-aqueous deficiency group. Similarly, temporal side LIPCOF showed a reliable positive correlation with dry eye disease severity grading in the non-aqueous deficiency group. However, this correlation was not statistically significant in the aqueous deficiency group. For the grade of nasal side LIPCOF, there was no statistical correlation between the conjunctival fold grade and the FBUT in all 76 eyes. However, there was a significant positive correlation between the conjunctival fold grade and the FBUT in the aqueous deficiency group. In the non-aqueous deficiency group, there was a significant negative correlation between the conjunctival fold grade and FBUT. For the total number of LIPCOFs, there was no statistical correlation between the total number of LIPCOFs and FBUT in all 76 eyes and the aqueous deficiency group. However, there was a significant negative correlation between the total number of LIPCOFs and FBUT in the non-aqueous deficiency group.